Software development for local area network control of laboratory instruments / Bariah Kariman - Kariman, Bariah (1999)
This thesis described the software developed to utilize the real time measurement using Local Area Network (LAN). An oscilloscope is used to obtain the measurement data from a test circuit having the input being supplied by a function generator. This test set is connected to a Personal Computer (PC), which is configured as the server, using an intelligent General Purpose Interface Bus (GPIB). The software is based on Microsoft's Visual Basic programming. By using this software, testing performed by the oscilloscope can be accessed by any client PCs in the same network.